Towards Online Shortest Path Computation Using Energy Based Clustering and Aggregation Algorithm - Sinthuja, S; Geetha, V (International Journal of Computer Sciences and Engineering, 2025)
The online briefest way issue aims at processing the briefest way based on live change circumstances. This is extremely imperative in present day car route frame lives up to expectations as it makes a difference drivers to make sensible decisions. To our best knowledge, there is no capable system/arrangement that can offer affordable costs at both customer and server sides on the other hand online briefest way computation. Unfortunately, the ordinary customer server building design scales poorly with the number of clients. A promising approach is to let the server gather live change information and at that point telecast them over radio on the other hand remote network. This approach has excellent versatility with the number of clients. Thus, we create a new framework called live change file (LTI) which empowers drivers to rapidly and effectively gather the live change information on the broadcasting channel. An impressive result is that the driver can compute/update their briefest way result by receiving just a little part of the index. The test study shows that LTI is robust to different parameters and it offers moderately short tune-in fetched (at customer side), quick question reactivity time (at customer side), little telecast size (at server side), and light support time (at server side) on the other hand online briefest way problem.